The awareness of occupational disease among employees / Muhamad Shafiq Muhd Maslan - Muhd Maslan, Muhamad Shafiq (Faculty of Business and Management, 2011)
Research study is the systematic and objective identification, collection, analysis, dissemination and use of information for the purpose of improving decision making related to the identification and solution of the problem. [Maholtra (2002)] The topic of the study, namely “The Awareness of Occupational Disease among Employees” can be divided into two outcomes which is high and low awareness. The 6 scope of study is all employees which covered under SOCSO and the areas of study are the whole nation of Malaysia. Under Occupational Safety and Health Act 1994, Act 514 Part 4 which explain the general duties of the employers and self employed person. Section 15 of this act legislated that the employers is responsible to provide a safe and healthy workplace for their employees. Section 16 of the same Act also stated that the employers need to enforce their safety and health policy and need to disclose information regarding any policy to all of their employees. Bases on this alone it should be safe to make an early assumption that there is a high awareness about occupational disease among employees since the enactment legislate the employers to do so. According to Lugah V et al (2010), “although the Occupational Safety and Health Act (OSHA) 1994 have existed in Malaysia for more than ten years, awareness of Occupational Safety and Health (OSH) remains relatively poor. Besides, awareness of OSH among healthcare professionals in Malaysia is very limited, and there have been only a few published research studies on OSH awareness.” This study show that just how much lack of awareness happen in our country. Even among healthcare professionals itself the awareness is poor. How do you aspect other type of profession to aware about the importance of health knowledge especially work related since we spent most of our time at workplace. If even healthcare professionals itself not fully aware of the importance of its, it will be worse for others workers such as labour workers which will be hard for them to be expose with this kind of knowledge. However the reason to do this research is due to the differences in the data collected from SOCSO reported about the occupational disease occur in Malaysia. Through this research we can determine either the awareness are high or low among the employees about occupational disease and whether they know what to do if suffering from its. Only after that we can suggest any corrective action if necessary and either the current level are satisfactory.